Liquidity indicators, fund utilization efficiency, and their impact on profitability in commercial banks - Alshehadeh, Abdul Razzak; Eid, Haneen Hussin Abu; Al-Khawaja, Haneen Aqel; Al Houl, Mohyi Aldin Abu; Jaradat, Mohammad Sulieman (International Journal of Innovative Research and Scientific Studies, 2025)
This research discusses the relationship between liquidity measures, namely, cash liquidity and legal liquidity, the legal reserve ratio on economic fund utilization as reflected in the granting of credit facilities, investments, and deposits, and their impact on profitability amongst the selected Jordanian commercial banks (JCB) that are listed on the Amman Stock Exchange (ASE). The applied methodology adopts financial reports and statements from 12 JCB during the period starting from 2011 to 2022. Analysis of the multiple measures of the methodologies used to test these relationships was done using multiple regression analysis as the main statistical tool. Results show a significant correlation between cash liquidity and legal liquidity measures and efficiency of funds utilization in the banks under review. Yet no statistically significant relationship was found between the legal reserve ratio and fund utilization efficiency. Furthermore, the study establishes a strong relationship between fund utilization efficiency and return on assets (ROA) and between cash liquidity and legal liquidity measures and ROA. On the other hand, the legal reserve ratio had no meaningful correlation with the ROA. These findings will help the JCB to keep a good balance between liquidity management and profitability maximization. Proper allocation of the existing liquidity level in lending to credit facilities and several investment opportunities is going to generate sustainable financial returns with perpetual cash flow. Moreover, the study suggests that an informed scientific approach to adequate fund allocation would enable banks to maximize profitability with an acceptable risk profile while complying with the liquidity requirements set forth by financial regulators. Such balance is important to become compliant with the guidelines set forth by the wider financial system towards ensuring financial stability and sustainability.